Puissance prismatique effective : Analyse parametrique - Lachance, Andre (Canadian Journal of Optometry, 2026)
A prismatic lens is required for an evaluation of ocular deviation. These lenses will induce a duction movement of the eye in order to follow the image. The study of this ocular movement will be a function of the interaction between parameters, such as the distance between the eye and the prismatic lense, and the distance between the object and the prismatic lense, related to the clinical manipulation of this prismatic lens. The effective prismatic power of a prismatic lense can be modified by the parameters. The prismatic effect of a prismatic lens on the ocular rotation will always be lower than the prismatic power of the lens, except for an object located at the optical infinity. If an equality is consdered between the prismatic value and the ocular rotation and the prismatic value of the lens, the error on the effective prismatic power will increase if the distance between object and lens decreases, or if the vertex distance increases.